Solitary Osteochondroma Arising from the Dorsal Vertebral Spinous Process: A Case Report - Joshi, Ruban Raj; Sundararaj, Gabriel David (Journal of Lumbini Medical College, 2016)
Introduction: Osteochondroma are benign tumors which arise from aberrant cartilage nodules within the periosteum. They can be either pedunculated or sessile and are more common in the extremities and rarely seen in spine. En-bloc excision is the preferred treatment. Case Report: We present a case of 20 year female, who came with a swelling and pain in lower back for two years which was diagnosed to be thoracic vertebra(D11) osteochondroma on x-ray and computed tomography. Excision biopsy was done and confirmed it to be osteochondroma. There has been no recurrence even after 16 months of follow up. Conclusion: Although rare, osteochondroma of the vertebra should be kept in mind as a differential diagnosis when evaluating mass in spine. En bloc excision should be performed. Journal of Lumbini Medical College. 2014;2(1):25-27.